Prevalence of Helicobacter pylori in adenotonsillar hypertrophy in children - Kraus, Jaroslav; Nártová, Eva; Pavlík, Emil; Katra, Rami; Šterzl, Ivan; Astl, Jaromír (Acta oto-laryngologica, 2014)
CONCLUSION: Our results encourage the notion that the pharynx could be an extragastric reservoir of Helicobacter pylori (HP). The study confirmed the presence of HP in adenotonsillar tissue in children. It could have importance in the pathophysiology of upper respiratory diseases. However, its precise role in these processes remains unclear and requires further studies. OBJECTIVE: A prospective study was carried out to evaluate the presence of HP in tonsillar and adenoid tissue in children. The study focused on real-time PCR analyzing CagA and VacA genotypes of HP strains. METHODS: A total of 37 consecutive pediatric patients with adenotonsillar hypertrophy indicated for surgery were observed in a prospective study. Adenoidectomy and/or tonsillectomy was performed in each patient; 49 specimens were taken, 32 from adenoids and 17 from tonsils. The presence of HP and its genotype were tested in all samples by real-time PCR analysis. RESULTS: Of 49 samples analyzed, 48 were positive for the presence of HP (98%), so only 1 sample was negative. While the genotype VacAs1bm2 was definitely dominant in adenoid tissue, wider distribution was observed in tonsillar tissue. Cag(+) strains represented one-fifth of all samples (21%).
Keywords: adenoidy; bakteriální proteiny; kvantitativní polymerázová řetězová reakce; Adenoids; Prospective Studies; Real-Time Polymerase Chain Reaction; antigeny bakteriální; předškolní dítě; Humans; Prevalence; prospektivní studie; Hypertrophy; Antigens, Bacterial; Czech Republic; Palatine Tonsil; mužské pohlaví; Česká republika; Helicobacter pylori; Child, Preschool; Helicobacter Infections; Bacterial Proteins; krční mandle; infekce vyvolané Helicobacter pylori; nemoci faryngu; ženské pohlaví; Pharyngeal Diseases; prevalence; dítě; Child; Male; Female